Active surveillance for emerging influenza A viruses – Findings from a One Health study in Vietnam’s live bird markets - Vuong N. Bui; Oguzie, J.U.; Tung D. Dao; Anh N. Bui; Son D. Tran; Quy D. Nguyen; Hung Q. Nguyen; Trujillo-Vargas, C.M.; Marushchak, L.V.; Thang Nguyen-Tien; Shittu, I.; Hung Nguyen-Viet; et al. (Elsevier, 2025)
Objectives: Live bird markets (LBMs) in Asia have often been the source of human infections with avian influenza virus (AIV).